Fungsi Badan Permusyawaratan Desa Di Desa Gela Kecamatan Taliabu Utara Kabupaten Pulautaliabu Provinsi Maluku Utara - Sahupala, Boliadi; Usman, Jaelan; Mone, Asyari (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to describe and explain the function of the VillageConsultative Agency (BPD) in Gela Village, North Taliabu District, Taliabu Island Regency, North Maluku Province. This study used qualitative research method with the type of descriptive research. Data collection techniques used observation, interviews and documentation. The results of this study showed that the function (BPD) was divided into 3 (three), namely: (1.) determining the draft Village regulations that had been implemented and realized well in infrastructure performance in development, (2.) accommodating and channeling the aspirations of the village community, which was less carried out well, this was because there were still obstacles in its implementation, where the community still did not understand the duties and functions carried out by the BPD, so that in the implementation process of accommodating and channeling the aspirations of the community they often got opposition and debate from the community, (3.) village supervision on the performance of the village head, which was not implemented properly, this was due to the lack of communication between the BPD management.Keywords: Function, Village Consultative Agency(BPD)